LEGAL LIABILITY FOR THE CRIME OF DATA THEFT IN FAKE JOB POSTINGS - Priyati, Sri; Sudarsono, Galih Putri; Sumartini, Sumartini; Permana, Dhewangga Bayu; Swastika, Putu Angga Elano (jfpublisher, 2024)
The rapid advancement of science and technology has made information technology a daily necessity, which contributes to improving the welfare of society by maintaining justice, certainty and legal expediency. In addition to the positive impacts caused, there are also negative impacts, one of which is in terms of personal data security. The focus of this research is the legal protection of job applicants as victims of criminal acts of data theft, as measured from the perspective of legal expediency. Law functions as a tool to achieve goals in society and the state, with the protection of human interests as the main focus. This research applies the empirical juridical method, which combines juridical aspects with actualities in the field on the basis of facts from research and observation. Criminal responsibility determines whether the defendant is responsible for a criminal offense that fulfills the elements of the offense. The criminal justice process follows the Criminal Procedure Code (KUHAP) and the Criminal Code (KUHP), which are the lex generalis in criminal law. The principle of Lex Specialis Derogat Legi Generali is applied to laws excluding the Criminal Code, as stipulated in Article 103 of the Criminal Code. Currently, the Electronic Information and Transaction Law is the reference; nevertheless, there are several obstacles related to the case of personal data theft. Therefore, the enactment of the Personal Data Protection Law is expected to be a solution in solving cases of personal data theft, especially those related to fake job postings.